Vibration Analysis and Optimization of a Rectangular Plate with Flanging Hyperellipse Cutout - Wensheng Wang; Sier Deng; Song Zhang; Da Geng (Shock and Vibration)
Vibration analysis and optimization of a rectangular plate with a flanging hyperellipse cutout is investigated in this paper, numerically. In the analysis, finite element method (FEM) is applied to perform parametric studies on various plates in different boundary conditions, addressing the influence of different cutout parameters (area, shape, flanging height, position, and rotation) on the first- and second-order natural frequencies of the rectangular plate and providing references for the optimum frequency design. Then, maximization of frequency or the difference of two consecutive frequencies of the rectangular plate is carried out using Multi-island Genetic Algorithm, aiming to achieve the best dynamic characteristics. The results show that different cutout parameters have great influence on vibration performance of the plate, the existing of the flanging increases the out-of-plane stiffness of the plate. Additionally, the nature frequency of the plate has been improved obviously for different models with the optimal design of the cutout.